Análisis de la gestión integral de residuos sólidos en la zona sur del área metropolitana del Valle de Aburra - 2004 (2004)
ABSTRACT: To evaluate the integrated management of solid residues in the south zone of Medellín Metropolitan Area. Methodology: a descriptive study was made to examine the socio-economical, technical, environmental and institutional conditions related to the municipality. Solid residues management through its different stages. Results: the analysis showed that the cleaning public service has been oriented mainly to collecting and transporting the residues to their final disposal, without considering the regular stages that should be an integral part of the solid residues process. A diagnosis permitted the identification of deficiencies and needs that were used for the study of alternatives to solutions and strategies facilitating the proposal of programs and projects aimed to improve residuals management from their generation to their final disposal. Conclusion: the need to implement permanent sensibilization and education campaigns oriented towards an attitudinal change in those involved in the municipal residual handling was identified. In addition, it is important to develop solution strategies for those people to take responsibility concerning local problems to get involved in an ongoing improvement of the previously mentioned managerial process.